The Social and Political Impact of Breach of Contract in Motor Vehicle Lease Agreements Based on the Indonesian Civil Code - Nova Ramadhani, Kania (Program Studi Politik Islam Universitas Islam Negeri Raden Fatah Palembang, 2024)
The relationship between companies and consumers is governed by binding agreements, intended to promote mutually beneficial cooperation and ensure smooth transactions. However, in practice, breaches of contract, such as delayed installment payments or violations of agreed terms, can occur. These breaches may have broader social and political implications, as they can affect consumer trust, economic stability, and the regulatory environment. This study aims to analyze the legal consequences of such breaches in motor vehicle lease agreements. Utilizing a normative legal research method with a qualitative descriptive approach, this research provides insights into the legal outcomes of defaults in motor vehicle lease agreements within the framework of the Civil Code. The study finds that the losing party in a civil case must bear the court costs. If there are multiple losing parties, the judge will determine how the costs are divided. This rule is important for ensuring legal certainty, preventing frivolous lawsuits, and ensuring that court proceedings are conducted fairly and efficiently.